The influence of capital requirement of Basel III adoption on banks' operating efficiency: Evidence from U.S. banks - Gabriel Ogunmola; Fengsheng Chien; Ka Yin Chau; Li Li (Journal of Central Banking Theory and Practice, 2022)
The United States is recognized as the largest economic entity in the world and its financial system has developed steadily through the guidance of the Federal Reserve System for over one hundred years. However, in recent years, the global economic downturn, coupled with the global COVID-19 pandemic, has led to an unprecedented economic depression and rapid decline in the United States financial sector. Although the U.S. government has gradually instructed banks to raise the core quantity but a giant crisis under the economic depression is still present. This study thus takes U.S. commercial banks as the subject of research and employs the two-stage bootstrapped truncated regression to investigate the impacts of increases in required Core, Tier 1, and total capital adequacy ratios on their efficiency.
Keywords: N12; G32; 330; Banking; Capital requirement; Operating efficiency; Two-stage DEA; Bootstrap